Cultural sustainability and Islamic perspectives in introducing a cohesive retirement village for Muslims - Abdul Majid, Noor Hanita; Denan, Zuraini; Hamidi, Mohd Hazwan (Elsevier, 2013)
The growing elderly population indicated a shift in the cultural context in Malaysia and the needs of elderly care facilities. This paper looks at the cultural sustainability issues and Islamic perspectives requirements through a review on the recommendations outlined in the Quran and Hadiths; surveys and case studies on the available elderly care facilities in Malaysia. The results indicated the perception of the respondents on the idea of having elderly care for the Muslim community and also the preferred type of care facilities. The research findings outlined the criteria for a cohesive retirement village for Muslims.